Fabrication techniques for an arrayed EIS biosensor - Meng Taing (2018)
Electrolyte-Insulator-Semiconductor (EIS) based biosensors are generally exposed to liquid media that contain biological or chemical entities of specific interest. Such sensors measure change in electrical parameters such as capacitance when charged species attach to the insulator layer. It is common for fluidic media to be contained to protect critical transducer components from liquid contact. Often the sensing region of the transducer is the only region in contact with liquid. This sensing region can be defined by a window in a passivation layer. Well established MEMS processes allow passivation using common spin-on based polymers. This sensing area can be defined by standard exposure, curing and developing techniques which are cost effective. This research focuses on fabrication of a multiarray EIS biosensor device to ensure critical sections of the transducer are protected from contact with liquid and to allow definable sensing regions using standard spin-on polymers. The sensor arrays were created by dicing the silicon-bulk into individual finger-like structures which serve as individual sensors. Bulk-silicon was anodically bonded to a glass support substrate to provide stability and serve as a platform for the sensors. Dicing allowed rapid separation of silicon-bulk compared to chemical or high energy milling techniques. A silicon oxide layer was grown on the silicon bulk to form the sensing layer. Charge based species in the liquid induce an electric field through the oxide. The depletion/space charge region below the oxide is modulated by the electric field which can be measured by capacitance. Specific layers can be attached to the oxide surface to create a sensor which responds to particular charged species. ©2009 IEEE.